The identities of Millettia pseudoracemosa and M. pulchra var. munnarensis (Fabaceae: Millettieae) from South India - Song, Zhu-Qiu (Phytotaxa, 2023)
Millettia pseudoracemosa and M. pulchra var. munnarensis were described as small trees with large and violet flowers from South India in 1997 and 2017, respectively. However, referring to literature and examination of herbarium specimens showed that both of the two taxa cannot be distinguished from with M. dura, a species described from tropical Africa in 1911. The species was widely cultivated in East Africa and also introduced to South India and Sri Lanka during the early 20th century. Thus, the former two names are reduced as synonyms of the last name. The lectotypes of M. dura and M. pseudoracemosa are also designated here. In addition, it is confirmed that 12 Millettia species are recorded from India, including eight native species and four introduced ones.